2002
DOI: 10.1097/00006123-200205000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Resection of Grade II Astrocytomas in the Superior Frontal Gyrus

Abstract: Surgery for Grade II gliomas in the superior frontal gyrus is more likely to result in permanent morbidity when the resection is performed at a distance of less than 0.5 cm from the precentral gyrus or positive stimulation points. Therefore, cortical mapping of motor and speech function, in critical cases under local anesthesia with the patient as his or her own monitor, is recommended; resection should be tailored to obtain good functional outcome and maintain quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 27 publications
5
37
0
Order By: Relevance
“…Presumably, any unnoticed white matter injury of the primary motor fibers, such as the corticospinal tract, could cause permanent motor weakness. Peraud et al 17 and Kasasbeh et al 7 showed that the distance between the resected area and the precentral gyrus was significantly related to both transient and permanent neurological impairments. Moreover, the anterior-posterior extent of the resected SMA was the most frequently reported risk factor of SMA syndrome in previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Presumably, any unnoticed white matter injury of the primary motor fibers, such as the corticospinal tract, could cause permanent motor weakness. Peraud et al 17 and Kasasbeh et al 7 showed that the distance between the resected area and the precentral gyrus was significantly related to both transient and permanent neurological impairments. Moreover, the anterior-posterior extent of the resected SMA was the most frequently reported risk factor of SMA syndrome in previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…233 Similarly, in neuro-oncological surgery, many patients display sequelae due to an interruption of the white matter fibers. 234,235 Consequently, during surgery in eloquent areas, the systematic use of intraoperative subcortical stimulation seems mandatory, to better understand underlying anatomo-functional connectivity 141,142,236 and to avoid postsurgical sequelae, which will always be possible despite cortical plastic potential. 237 …”
Section: Surgical Resectionmentioning
confidence: 99%
“…Near-complete functional recoverability from injury is expected, usually occurring within 4 to 8 weeks (45). However, subtle underutilization of contralateral limbs or delay in speech initiation may persist.…”
Section: Functional Topography Of Premotor Areasmentioning
confidence: 99%